Pengaruh Environmental, Social, And, Governance dan Kekuatan Chief Executive Officer Terhadap Kinerja Keuangan Perbankan di BEI - Nur Asrin; Ramly, Ramly; Ismawati, Ismawati (Jurnal Riset Rumpun Ilmu Ekonomi, 2025)
The purpose of this study is to explain the influence of Environmental Social Governance (ESG) and the power of the Chief Executive (CEO) on the financial performance of banking companies on the IDX during the period 2023-2023. . Environmental Social Governance (ESG) is becoming a new standard in the investment world, requiring companies to be more responsible for the environment, social, and good corporate governance practices can increase public trust, one of which is by implementing ESG which has been proven to be a trigger for sustainable business growth, while the CEO is the president director or main director in a company and has obligations for the tasks and success of the business. This study uses a quantitative research method with a descriptive verification technique. The research sample consisted of 22 companies. ESG is measured using a dummy variable with a value of 1, CEO power is measured based on the length of tenure, and the company's financial performance is measured using Return On Asset (ROA). Based on the results of the analysis conducted, the results obtained indicate that (1) ESG has a negative effect on financial performance. (2) CEO power has a positive effect on the company's financial performance.